Towards New Classes of Intelligent Cognitive Information Systems for Semantic Pattern Classification - Ogiela, Marek R.; Ogiela, Lidia (Computing and Informatics, 2012)
This paper introduces two new classes of specialised vision systems called UBIAS and E-UBIAS. Such systems belong to the group of cognitive reasoning systems and are designed for the semantic analysis of visual patterns in the form of medical images. Proposed systems are predecessors of a new generation of intelligent systems dedicated for understanding medical diagnostic visualization and using this data as biometric characteristics.